2010
DOI: 10.1021/ic902181e
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Resonance Vibrational Spectroscopy Applied to [Fe(OEP)(NO)]: The Vibrational Assignments of Five-Coordinate Ferrous Heme−Nitrosyls and Implications for Electronic Structure

Abstract: This study presents Nuclear Resonance Vibrational Spectroscopy (NRVS) data on the fivecoordinate (5C) ferrous heme nitrosyl complex [Fe(OEP)(NO)] (1, OEP 2− = octaethylporphyrinato dianion) and the corresponding 15 N 18 O labeled complex. The obtained spectra identify two isotope sensitive features at 522 and 388 cm −1 , which shift to 508 and 381 cm −1 , respectively, upon isotope labeling. These features are assigned to the Fe-NO stretch ν(Fe-NO) and the in-plane Fe-N-O bending mode δ ip (Fe-N-O), the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 79 publications
7
66
0
Order By: Relevance
“…Thus, regardless of the common opinion [42], hybrid functionals appear to be the best for description of complex I geometry. It should be noted that such results have been recently observed for other mononuclear nitrosyl iron complexes [43].…”
Section: Geometry Optimizationsupporting
confidence: 80%
“…Thus, regardless of the common opinion [42], hybrid functionals appear to be the best for description of complex I geometry. It should be noted that such results have been recently observed for other mononuclear nitrosyl iron complexes [43].…”
Section: Geometry Optimizationsupporting
confidence: 80%
“…DFT calculations for [Fe(OEP)(NO)] suggest that peripheral group conformations can have significant effects on the lower frequency regions as well. 78 …”
Section: Discussionmentioning
confidence: 99%
“…This study found the heterolytic cleavage pathway for the ðBLMÞFe III ─ H 2 O 2 complex to be thermoneutral and therefore feasible. Because ABLM is inaccessible to vibrational characterization by resonance Raman (rR) spectroscopy due to photodecay (16), we employed nuclear resonance vibrational spectroscopy (NRVS) (17)(18)(19)(20) to obtain vibrational information and define the axial ligands of Fe III BLM and ABLM, thus distinguishing between possible reaction mechanisms.…”
mentioning
confidence: 99%